Ответ:
Объяснение:
a)
[tex]xy+xz+y+z=y+xy+z+xz=y(1+x)+z(1+x)=(y+z)(1+x)[/tex]
б)
[tex]m+kn+n+km=m+km+n+kn=m(1+k)+n(1+k)=(m+n)(1+k)[/tex]
в)
[tex]m-kn+n-km=m-km+n-kn=m(1-k)+n(1-k)=(m+n)(1-k)[/tex]
г)
[tex]mn+5n+5k+km=5k+km+5n+mn=k(5+m)+n(5+m)=(k+n)(5+m)[/tex]
д)
[tex]a^3+a^2-5a-5=a^2(a+1)-5(a+1)=(a^2-5)(a+1)[/tex]
е)
[tex]b^3+3b^2+2b+6=b^3+2b+3b^2+6=b(b^2+2)+3(b^2+2)=(3+b)(b^2+2)[/tex]
ж)
[tex]b^3-3b^2-2b+6=b^3-2b-3b^2+6=b(b^2-2)-3(b^2-2)=(b-3)(b^2-2)[/tex]
з)
[tex]y^3-by^2+3b^2y-3b^3=y^3-by^2-3b^3+3b^2y=y^2(y-b)+3b^2(y-b)=(3b^2+y^2)(y-b)[/tex]
и)
[tex]35x^2+35xy+20x+20y=35x^2+35xy+20x+20y=35x(x+y)+20(x+y)=(35x+20)(x+y)[/tex]
к)
[tex]8x^2-12xy+14xz-21yz=4x(2x-3y)+7z(2x-3y)=(4x+7z)(2x-3y)[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
a)
[tex]xy+xz+y+z=y+xy+z+xz=y(1+x)+z(1+x)=(y+z)(1+x)[/tex]
б)
[tex]m+kn+n+km=m+km+n+kn=m(1+k)+n(1+k)=(m+n)(1+k)[/tex]
в)
[tex]m-kn+n-km=m-km+n-kn=m(1-k)+n(1-k)=(m+n)(1-k)[/tex]
г)
[tex]mn+5n+5k+km=5k+km+5n+mn=k(5+m)+n(5+m)=(k+n)(5+m)[/tex]
д)
[tex]a^3+a^2-5a-5=a^2(a+1)-5(a+1)=(a^2-5)(a+1)[/tex]
е)
[tex]b^3+3b^2+2b+6=b^3+2b+3b^2+6=b(b^2+2)+3(b^2+2)=(3+b)(b^2+2)[/tex]
ж)
[tex]b^3-3b^2-2b+6=b^3-2b-3b^2+6=b(b^2-2)-3(b^2-2)=(b-3)(b^2-2)[/tex]
з)
[tex]y^3-by^2+3b^2y-3b^3=y^3-by^2-3b^3+3b^2y=y^2(y-b)+3b^2(y-b)=(3b^2+y^2)(y-b)[/tex]
и)
[tex]35x^2+35xy+20x+20y=35x^2+35xy+20x+20y=35x(x+y)+20(x+y)=(35x+20)(x+y)[/tex]
к)
[tex]8x^2-12xy+14xz-21yz=4x(2x-3y)+7z(2x-3y)=(4x+7z)(2x-3y)[/tex]